Worker beliefs about outside options - Simon Jäger; Christopher Roth; Nina Roussille; Benjamin Schoefer (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
Workers wrongly anchor their beliefs about outside options on their current wage. In particular, low-paid workers underestimate wages elsewhere. We document this anchoring bias by eliciting workers' beliefs in a representative survey in Germany and comparing them to measures of actual outside options in linked administrative labor market data. In an equilibrium model, such anchoring can give rise to monopsony and labor market segmentation. In line with the model, misperceptions are particularly pronounced among workers in low-wage firms. If workers had correct beliefs, at least 10% of jobs, concentrated in low-wage firms, would not be viable at current wages.
Keywords: D83; D84; 330; Beliefs; Outside Options; Information Frictions; Sorting